Zarathustra's maxim - Pino Posada, Juan Pablo (Estudios de Filosofía, 2003)
The article goes through Thus Spoke Zarathustra exploring the peculiarities of its writing. It intends to answer specifically to the question about how doctrinal content —Zarathustra's teaching— Is interwoven with the way chosen by Nietzsche to communicate it: the maxim. In order to do this, the speech On Reading end Writing is taken as a starting point. This speech addresses explicitly the issue communication with the reader and besides, it refers implicitly to the moment when this communication reaches crisis point, ie. when the doctrine of eternal return is taught Consideration of this critical point shows that, in order to account for the peculiar configuration of Zarathustra saying, it is necessary to postulate an alternative to the notion of semi-poetic discourse. The article intends to deal with this need by highlighting the concept of maxim and by showing how the conditions for us audition are not different from that place thought by Nietzsche for his work.